Publlc service delivery in education: the BRAC experience - Ahmed, Salehuddin; Nath, Samir Ranjan (BRAC Research and Evaluation Division (RED), 2020)
BRAC, a non-governmental development organisation in Bangladesh, has been working for the socio-economic advancement of the poor, especially the women and children. It has long experience in providing basic public health services, enhancing income earning activities, and extending education. Complementary to the State initiatives, alternative public service delivery systems became relevant in many countries. This paper explores BRAC experiences in providing basic and primary educational services to the poorer section of the community. Starting with a functional literacy programme for the adult people how BRAC turned into a quality primary education provider for the children and adolescents was explored in this article. Activities on other components like continuing education, adolescent development and secondary education are also discussed. It also showed how BRAC's countrywide network, research, monitoring, accounts and audit departments - which in general are not considered as educational activities - played important roles in making the education programme grounded and expanded. Lessons learn from this experience are also summarized.